Comparison of growth rate and viability of DF-1 cell line in different culture media - Arifin, Mohd Azmir; Mel, Maizirwan; Ahmad Raus, Raha; S. H., Sharifah; Ideris, Aini (2008)
One of the commercial cell line that gained attention for the study of viral vaccine was an immortalized cell line derived from chicken embryo fibroblast (CEF) cells. Unlike CEF cells, DF-1 cells have higher proliferation rate and also can be subcultured infinite number of times. In this study, the growth profile of DF-1 cell line was investigated by undergoing series of optimization process by testing it out on several culture media and also by manipulating the components of culture media which were sodium bicarbonate and serum. At the end of this study it has been figured out that DF-1 achieved the highest cell culture density in Dulbecco’s Modification of Eagle’s Medium( DMEM) and with 1.24 g/L of NaHCO3 and 5.5 % serum, it yielded the shortest doubling time.